Schizophrenia; A Review on Promising Drug Delivery Systems - Bülbül, Ece Ö.; Karantas, Ioannis D.; Okur, Mehmet E.; Siafaka, Panoraia I.; Okur, Neslihan Ü. (Current Pharmaceutical Design, 2020)
Background: Schizophrenia belongs to mental illnesses affecting 1% of the worldwide population. Its therapy is still unmet; thus, researchers aimed to develop new pharmacological molecules which can improve its management. Methods: Moreover, the current typical and atypical antipsychotics should be formulated in more efficacious systems that can deliver the drug in the brain with as few side effects as possible. Further, the development of long-acting efficient drug delivery systems could be significant in minimizing frequent dosing which is nonpreferred to schizophrenics. Results: Herein, authors focused on current developments of antipsychotic medications used in schizophrenia management. Various studies, which include the use of first and second-generation antipsychotics, were analyzed according to their efficacy. In fact, in this review, oral, injectable, transdermal and intranasal formulations entrapped antipsychotics are presented to be valuable guidance for scientists to formulate more effective drug delivery systems for schizophrenic patients. Conclusion: This review aimed to assist researchers working on schizophrenia management by summarizing current medications and newly synthesized drug delivery systems recently found in the literature.
Keywords: Schizophrenia